Analysis of The Effectiveness of Project Management Skill of Human Resources At PT. Ecart Webportal Indonesia - Febriana, Widia; Anggriani, Rini; Yoga Sumadewa, I Nyoman; Cahyadi, Irwan (Sumber Belajar Sejahtera, 2024)
This article investigates the Project Management Skill of human resources at PT Ecart Webportal Indonesia, this research Studied related to Lazada Social Sharing Qualitative Research which contains awareness and engagement of Lazada users on game platforms such as Share Pocket, lazget, lazcuan. and digitization, exploring current practices. challenges, and future trends. This article starts with project management skills at Lazada, emphasizing the important role of IT projects, IT project management in managing technology transformation. Coupled with the importance of management's role in improving the quality of human resources (HR) in the context of modern organizations. Comprehensive insights on Lazada Social Sharing Qualitative Research containing Lazada users' awareness and engagement towards gaming platforms such as Share Pocket, lazget, and lazcuan, models, and success metrics are provided through an extensive literature review. Challenges such as not innovating against change in the era of globalization, Interoperability, resistance to change, along with strategic solutions. The article also outlines best practices, emphasizing collaborative stakeholders, agile methodologies, and continuous evaluation. Future trends, including Lazada users' awareness and engagement of gaming platforms such as Share Pocket, lazget, and lazcuan.offer a forward-looking perspective. In conclusion, Project Management Skill human resources, the importance of the role of management in improving the quality of human resources (HR) in the context of modern organizations. Related to Lazada Social Sharing Qualitative Research which contains awareness and engagement of Lazada users on game platforms such as Share Pocket, lazget, and lazcuan and Digitalization.